An Equitable and Sustainable Development model in the era of global crises - Di Salvo, Michele (Revista de Estudios Socioeducativos. ReSed, 2025)
This essay is developed on several levels and in several stages. In a first step, we will address the hermeneutic question of the theme of 'equitable and sustainable development'. The theme of the 'crisis' will be addressed through the dual economic and social levels in the context of a development model of globalised capitalism. Considering the concept of crisis not only as an "occasional transformation" but as a constant and endemic element of the capitalist economic model in the era of globalised finance and markets, a psychiatric diagnosis of this model and its active subjects, the corporations, will be proposed, and we will see, thanks to Fromm, how this pathology extends to the "so-called normal". Finally, two possible revision blocks will be put forward at the same time. The first of the very concept of growth and development by considering different models than GDP. The second, using an inverse psychology method, a framework of measures that materialise this redefinition of parameters. What needs to be rethought, then, are not just development models, but the very concepts of a new anthropological physics: human space and time.